A different kind of activism: the position of catholic women teachers in their union (Belgium, 1950-1965) - Rompaey, Lies van; Depaepe, Marc; Simon, Franck (Sens public, 2009)
In this article we would like to focus on the position of women in the Christian teachers union in Belgium in the years 1950-1965. In spite of their numerical dominance in the teaching occupation and in the union, women teachers never exercised real structural power in teacher unionism during this period. Yet, the union was alive to the fact that women teachers formed an important segment of their members. The marriage bar f.e. became a central issue in the debate concerning the legal statute of the catholic teachers in the years 1961-1963. Based on primary sources, interviews, national and international literature, we will focus on the apparent lack of female militantism by situating it in its social and historical context and by analysing the prevailing ideology concerning labour and the family.